Mobility of non-permanent workers and energy consumption in Indonesia - Mulyani, Karina Indah; Hartono, Djoni; Misdawita, Misdawita (Universitas Ahmad Dahlan, 2025)
Expensive land in urban centers encourages workers to migrate to the suburbs, creating worker mobility that increases energy consumption and worsens environmental quality. Therefore, understanding the relationship between worker mobility and energy consumption is crucial. This study evaluates the impact of worker mobility categorized as commuter and circular on energy consumption in Indonesia. We used the Extended Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model with instrumental variables (IV) on panel data from 33 provinces during the 2013–2018 period. The results show that commuter workers do not significantly affect total energy and fuel consumption, but significantly increase electricity consumption. Conversely, circular workers contribute significantly to increased total energy, fuel, and electricity consumption. Other impacts include decreased health and disruption to social life, despite the economic benefits. This study contributes to the literature on labor and energy in developing countries, particularly regarding the aspect of non-permanent workers. These findings are also relevant as a basis for formulating sustainable development policies that consider economic, social, and environmental aspects in a balanced manner.